2022
DOI: 10.30919/esee8c744
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on Magnetic Separable Spinel as a Promising Materials for Photocatalysis and Waste Water Treatment

Abstract: In the recent times, the demand of the energy and the environmental pollution is the main concern of the global. Due to their significant chemical, physical and magnetic properties spinel-based materials are prominently used in the field of photocatalysis and water splitting. In the present report is emphasis on the fundamental's understandings for their size, shape, chemical and the degradation of various pharmaceutical drugs, pesticides, and textile dye materials. This report explained the way of formation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…Xiaoxing Xu et al reported enhanced H 2 performance with Ga-doped ZnFe 2 O 4 , where Ga doping created trap states between the energy levels, hence increasing charge migration and band gap energy compared with the parent ZnFe 2 O 4 [67]. There is a strong correlation between catalytic activity and crystal structures along with all the physicochemical properties [68]. Moreover, the high-temperature calcination required for the pure-phase formation of spinel ferrite can eliminate the trapping sites for electrons and holes and hence can be avoided to decrease the recombination rates.…”
Section: Synthesis Approachesmentioning
confidence: 99%
“…Xiaoxing Xu et al reported enhanced H 2 performance with Ga-doped ZnFe 2 O 4 , where Ga doping created trap states between the energy levels, hence increasing charge migration and band gap energy compared with the parent ZnFe 2 O 4 [67]. There is a strong correlation between catalytic activity and crystal structures along with all the physicochemical properties [68]. Moreover, the high-temperature calcination required for the pure-phase formation of spinel ferrite can eliminate the trapping sites for electrons and holes and hence can be avoided to decrease the recombination rates.…”
Section: Synthesis Approachesmentioning
confidence: 99%
“…It was previously found that CuFe 2 O 4 NPs were a 75% efficient photocatalyst for rhodamine B dye. 35 Since the physical properties of CuFe 2 O 4 nanoparticles such as phase transitions, electrical switching, semi-conductivity, magnetic properties, and chemical stability can alter in response to varying environmental circumstances, they are the ideal spinel ferrite. 36 CuFe 2 O 4 nanoparticles have been employed in the production of lithium-ion rechargeable batteries, magnetic resonance imaging materials, photocatalysts for hydrogen evolution using visible light, energy storage materials, coupling reaction catalysts, CO 2 reduction catalysts, photoanodes for solar water oxidation, supports for enzyme immobilization, and catalysts in nanomedicine for the treatment of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The metal oxides are mixed in the form of a powder and then sintered in a furnace to form a ceramic material. Spinel ferrites are represented by a general formula AFe 2 O 4 , where A refers to the divalent metal cations [Ni 2+ , Cu 2+ , Mn 2+ , Zn 2+ , Co 2+ , etc], can be depicted as a closely packed cubic structure of oxygen atoms with A 2+ and Fe 3+ at two different crystallographic regions [1,2]. These regions are labelled as tetrahedral (A-site) and octahedral (B-site) oxygen coordination, respectively.…”
Section: Introductionmentioning
confidence: 99%